Partisipasi Masyarakat terhadap Pembangunan Sarana Lingkungan Permukiman di Balangnipa - Muhlis Hajar Adiputra; Muhammad Erwin Syukri; Rizki Mulya R (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
This paper aims to find out what factors influence the low level of community participation and efforts to increase community participation in the construction of residential environmental facilities in Balannipa Village. This type of research is quantitative research with a population of 100 respondents using probability sampling. Data analysis techniques using the Chi-Square Test and SWOT analysis. The results of this study explain that of the 6 variables analyzed, the factors that influence low community participation are age (X1) and type of work (X4), so that efforts to increase community participation are formulated, namely budget transparency, overseeing and supervising the use of allocated funds, maximizing manpower and time owned, all forms of aspirations and ideas must be accommodated, considered, and evaluated, manage and maintain facilities, infrastructure, and/or public service facilities in an effective, efficient, transparent, and accountable and sustainable and responsible manner, in the process of exemption land, referring to the Regulation of the President of the Republic of Indonesia No. 36 of 2005 Chapter II Article 4 (1) Concerning Land Acquisition, as well as constructing environmental facilities by paying attention to environmental sustainability aspects life.